POTENSI JAMUR ENDOFIT TANAMAN KARET DALAM MENGHAMBAT PERTUMBUHAN JAMUR AKAR PUTIH (Rigidoporus microporus) SECARA IN VITRO - Widya Lestari (JURNAL AGROPLASMA, 2019)
One of the environmentally friendly control alternatives that can be done, namely by utilizing biological agents in the form of endophytic fungi that are antagonistic. This study aims to study and obtain information about the potential of endophytic fungi in inhibiting white root fungi in vitro. Endophytic fungi isolation is carried out by sterilizing the surface of the stem of the rubber plant and culture it on agar nutrient media. Five endophytic bacterial isolates were obtained from the roots of rubber plants, respectively: JEB01, JEB02, JEB03, JEB04 and JEB05. Fungal isolates were tested antagonistically in vitro against Rigidoporus microporus. Two fungal isolates, JEB01 and JEB02 showed the best antagonist in inhibiting the growth of pathogenic fungi Rigidoporus microporus in vitro. Keywords: endophytic fungi, in vitro, Rigidoporus microporus, rubber plants (Hevea brasilliensis